Cognitive and behavioural strategies for self‐directed weight loss: systematic review of qualitative studies. (24th January 2017) - Hartmann‐Boyce, J.; Boylan, A.‐M.; Jebb, S. A.; Fletcher, B.; Aveyard, P.
Summary: Aim: We conducted a systematic review of qualitative studies to examine the strategies people employ as part of self‐directed weight loss attempts, map these to an existing behaviour change taxonomy and explore attitudes and beliefs surrounding these strategies. Methods: Seven electronic databases were searched in December 2015 for qualitative studies in overweight and obese adults attempting to lose weight through behaviour change. We were interested in strategies used by participants in self‐directed efforts to lose weight. Two reviewers extracted data from included studies. Thematic and narrative synthesis techniques were used. Results: Thirty one studies, representing over 1, 000 participants, were included. Quality of the included studies was mixed. The most commonly covered types of strategies were restrictions, self‐monitoring, scheduling, professional support and weight management aids. With the exception of scheduling, for which participant experiences were predominantly positive, participants' attitudes and beliefs surrounding implementation of these groups of strategies were mixed. Two new groups of strategies were added to the existing taxonomy: reframing and self‐experimentation. Conclusions: This review demonstrates that at present, interventions targeting individuals engaged in self‐management of weight do not necessarily reflect lived experiences of self‐directed weight loss.